An Empirical Study Of Business Owners' Personal Characteristics, Business Strategies And Companies' Performance Among Contractors Of Telekom Malaysia Berhad - Chong, Siong Choy (2000)
This project paper attempts to examine the co-relationship between entrepreneurs' personal characteristics, values, business strategies and company financial performance among the Telekom Malaysia Berhad contractors in Malaysia. Based on the previous empirical findings and theoretical literature, a research framework has been adopted to test the proposed correlation. All the one hundred and twenty four contractors in Malaysia were selected to participate in this study. Questionnaires were distributed to all the 124 Telekom Malaysia Berhad contractors in Malaysia using mail survey technique. The response rate was 57.3 percent ( 71 out of 124). The findings in this research may provide Telekom Malaysia Berhad with sufficient information to develop addition or new guidelines in selecting potential contractors in the future.